CONNEXITY AS A CONDITION FOR THE CREATION OF THE RIGHT OF RETAINING POSSESSION IN COMPARATIVE LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The subject of the work is a critical analysis and evaluation of the condition of connexity, i.e. thelegal connection that exists between the secured claim and the debtor's property, which certain foreignregulations standardize as a necessary condition for the establishment of right of retaining possession (iusretentionis). At the opposite pole is Serbian law, as well as the regulations from neighboring countries,which in their legal texts have completely eliminated the condition of connexity in the adopted concept ofa single regulation of civil and commercial right of retaining possession. The aim of the paper is: locatingdifferent types of connexity in comparative law, then classifying different models of regulation in relationto this condition, as well as finding reasons for the domestic legislator's waiver of the condition, which wasa prerequisite for the emergence of civil retention in Serbian law for a long time (until the adoption of theLaw on Obligations). The author assesses that the condition of connexity is part of the legal tradition ofthose regulations that separately regulate civil and commercial right of retention, but that the best solutionis the one that completely eliminates connexity. It is in line with: the modern tendency to maximize thescope of retention based on the easy conditions of establishment; with the solutions of new regulations,which do not introduce this condition; with domestic positive law; and finally, in accordance with the solution of European Union "soft law", which the national solution should be harmonized with.
Keywords: right in rem; right of retaining possession; connexity; civil and commercial ius retentionis.